Enterprise management strategies in agricultural fairtrade products - Xavier Lawrence D. Mendoza; Jerico B. Tadeo; Jaypee M. Dacanay; Arnold Nicholas Marla; Chiel Aszhnie B. Vergara (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — One of the fairtrade's major purposes is to raise the socio-economic of small-scale farmers. Numerous studies have found that fairtrade has a beneficial effect on farmers' profitability. Meanwhile, this study focused on the product management strategies of enterprises engaged in fair trade products.Method — The researchers used 50 legally registered enterprises located and operated in the province of Cavite. The significant findings were drawn and analyzed using a descriptive research design.Result — It was discovered that the majority of respondents were sole proprietors with few employees, had been in business for less than three years, and had an average initial capital of Php 3,000,000.00 or less. The product management strategies were very effective, and the majority of the participants used package labeling, fair pricing, and personal branding. Furthermore, the study identified challenges encountered in the implementation of product management strategies, such as poor consumer knowledge about packaging, financial resources that affect product pricing, and consumers' lack of brand exposure.Contribution — The study provides detailed product management practices or strategies among fairtrade products, which will serve as a springboard for status quo analysis and baseline studies to explore and develop pandemic- and post-pandemic-sensitive resilient strategies that will promote the sustainability of fairtrade enterprises.